Effects of Hospital Systems on Medical Home Transformation in Primary Care Residency Training Practices. Issue 3 (July 2017) - Knierim, Kyle; Hall, Tristen; Fernald, Douglas; Staff, Thomas J.; Buscaj, Emilie; Allen, Jessica Cornett; Onysko, Mary; Dickinson, W. Perry
Abstract : Most primary care residency training practices have close financial and administrative relationships with teaching hospitals and health systems. Many residency practices have begun integrating the core principles of the patient-centered medical home (PCMH) into clinical workflows and educational experiences. Little is known about how the relationships with hospitals and health systems affect these transformation efforts. Data from the Colorado Residency PCMH Project were analyzed. Results show that teaching hospitals and health systems have significant opportunities to influence residency practices' transformation, particularly in the areas of supporting team-based care, value-based payment reforms, and health information technology.